2007
DOI: 10.1007/s11434-007-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and property of high-performance Ag-Pb-Sb-Te system semiconducting thermoelectric materials

Abstract: High performance Ag-Pb-Sb-Te system thermoelectric bulk materials were fabricated by a combination of mechanical alloying (MA) and spark plasma sintering (SPS). Phase composition and microstructure of the resultant materials were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. A special emphasis was paid to the effects of chemical composition, especially the Pb content on the thermoelectric properties of the Ag 0.8 Pb 18+x SbTe 20 samples, including electrical resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…The phase structure of the obtained bulk sample was kept unchanged after annealing. Although the present compound was the optimized composition showing the best thermoelectric properties for MA and SPS by our previous study, it is worth noting that the Pb content in the Ag 0.8 Pb 22.5 SbTe 20 compound is richer than that of the stoichiometric composition for the AgPb m SbTe 2+ m system. As a result, some weak diffraction peaks of Pb were observed in the XRD patterns even for some annealed samples, although the intensity of Pb diffraction peaks decreased after annealing.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The phase structure of the obtained bulk sample was kept unchanged after annealing. Although the present compound was the optimized composition showing the best thermoelectric properties for MA and SPS by our previous study, it is worth noting that the Pb content in the Ag 0.8 Pb 22.5 SbTe 20 compound is richer than that of the stoichiometric composition for the AgPb m SbTe 2+ m system. As a result, some weak diffraction peaks of Pb were observed in the XRD patterns even for some annealed samples, although the intensity of Pb diffraction peaks decreased after annealing.…”
Section: Resultsmentioning
confidence: 67%
“…The milling was performed at 350 rpm for 4 h, and the MA-derived Ag 0.8 Pb 22.5 SbTe 20 powders were consolidated by SPS at 673 K for 5 min under an axial pressure of 50 MPa. The MA and SPS parameters were confirmed to be suitable for synthesizing the compound from the elemental powders by our previous studies. , The sintered bulk samples were sealed in vacuum (1 × 10 -3 Pa) in glass tubes and annealed for several days (3, 10, and 30 days) at 653 K.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…[ 15,24 ] As revealed by the XRD results shown in Figure 2 , a tiny amount of Pb phase remained in the OM sample, although its nominal composition of AgPb 22.5 SbTe 20 was optimized by previous studies. [ 25,27 ] The TEM observation also confi rmed the existence of Pb phase as nanosized and round-shaped particles as shown in Figure 4 ; the energy dispersive X-ray spectroscopy (EDS) data confi rmed that the nanoparticles are mainly composed of Pb element. The diameters of Pb nanoparticles range from 50 to 200 nm, which were observed both inside grains and at the grain boundaries.…”
Section: Full Papermentioning
confidence: 78%
“…However, our previous studies [ 25,26 ] revealed that excessive Pb is necessary for the MA-SPS-processed LAST materials that have a high thermoelectric performance due to a Pb loss during MA and SPS processes, which results in high electrical resistivity. The present AgPb 22.5 SbTe 20 composition for the MA and SPS process was optimized by our previous studies, [ 25,27 ] but it greatly depended on the purity of Pb powders as revealed by a more recent study. [ 28 ] Nevertheless, as shown in Figure 2 a,b, Pb peaks were not detectable in the sample after repeating milling and SPS, but the main cubic PbTe phase (F m3m ) is preserved no matter how long the second milling was conducted.…”
Section: Full Papermentioning
confidence: 99%